New species of Lachesilla (Psocodea: Psocomorpha: Lachesillidae), in species group corona, from southern Mexico and Central America - Aldrete, Alfonso N. García (Zootaxa, 2017)
Sixteen species of Lachesilla in species group corona are here described and illustrated. Five of them are endemic to Guatemala, one each are endemic to Costa Rica and Panama, four and three species respectively are endemic to the Mexican states of Chiapas and Oaxaca, and two species are shared by Chiapas and Guatemala.